Hydroxychloroquine and Mortality Among Patients With Systemic Lupus Erythematosus in the General Population. Issue 8 (7th July 2021) - Jorge, April; McCormick, Natalie; Lu, Na; Zheng, Yufei; Esdaile, John; De Vera, Mary; Choi, Hyon; Aviña‐Zubieta, J. Antonio
Abstract : Objective: Hydroxychloroquine (HCQ) has been associated with improved survival among patients with systemic lupus erythematosus (SLE) from tertiary referral centers. We aimed to determine the potential impact of HCQ use on the risk of mortality among SLE patients in the general population. Methods: We conducted a nested case–control study within an incident SLE cohort from the entire population of British Columbia, Canada. Deceased patients were matched with up to 3 living controls by age, sex, and SLE disease duration. HCQ exposure was categorized by the time between the last HCQ prescription date covered (i.e., end of supply) and the index date (i.e., death date) as current (<30 days), recent (30–365 days), remote (>365 days), or never used. We used conditional logistic regression to assess the risk of all‐cause mortality associated with current or recent HCQ exposure compared with remote HCQ users. Results: Among 6, 241 patients with incident SLE, we identified 290 deceased patients and 502 matched SLE controls. Adjusted odd ratios for all‐cause mortality were 0.50 (95% confidence interval [95% CI] 0.30–0.82) for current users and 2.47 (95% CI 1.21–5.05) for recent users compared with remote users. Associations were similar in subgroups according to SLE duration (≤5 years versus >5 years). Conclusion: Our general population data support a substantial survival benefit associated with current HCQ use. Increased mortality among patients who had discontinued HCQ recently could be due to a sick stopper effect or the loss of actual HCQ benefits.